Biomechanical analysis of prey capture in the carnivorous Southern bladderwort (Utricularia australis) - Poppinga, Simon (Sci Rep, 2017)
We recorded capture events (CEs) of the daphniid Ceriodaphnia dubia by the carnivorous Southern bladderwort with suction traps (Utricularia australis). Independent to orientation and behavior during trap triggering, the animals were successfully captured within 9 ms on average and sucked in with velocities of up to 4 m/s and accelerations of up to 2800 g. Phases of very high acceleration during onsets of suction were immediately followed by phases of similarly high deceleration (max.: −1900 g) inside the bladders, leading to immobilization of the prey which then dies. We found that traps perform a ‘forward strike’ during suction and that almost completely air-filled traps are still able to perform suction. The trigger hairs on the trapdoors can undergo strong bending deformation, which we interpret to be a safety feature to prevent fracture. Our results highlight the elaborate nature of the Utricularia suction traps which are functionally resilient and leave prey animals virtually no chance to escape.